The Inviscid Limit Behavior for Smooth Solutions of the Boussinesq System - Junlei Zhu (Abstract and Applied Analysis)
The inviscid limit problem for the smooth solutions of the Boussinesq system is studied in this paper. We prove the Hs convergence result of this system as the diffusion and the viscosity coefficients vanish with the initial data belonging to Hs. Moreover, the Hs convergence rate is given if we allow more regularity on the initial data.